Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Industri Fashion Online pada Merek H&M - Refany Novia Siboro (Journal of Management and Creative Business, 2024)
The research objectives include (1) This research aims to analyze the influence of product quality on purchasing decisions (2) This research aims to analyze the influence of brand image on purchasing decisions (3) This research aims to analyze the influence of product quality and image Brands on Purchasing Decisions..Research conducted by the Online Fashion Industry on the H&M Brand. The sample selection used used a purposive sampling method. The aim of the research was to determine the influence of product quality and brand image on purchasing decisions in the online fashion industry for the H&M brand. The results of the research on Product Quality partially have a positive and significant effect on purchasing decisions in the Online Fashion Industry for H&M Products (1). Brand Image partially has a positive and significant effect on Online Fashion Industry Purchasing Decisions on H&M Products (2). Product Quality and Brand Image simultaneously have a positive and significant influence on Online Fashion Industry Purchasing Decisions on H&M Products (3).